Kemampuan Pemecahan Masalah Matematika Terintegrasi Islam Siswa Diskalkulia Berdasar Teori Polya - Khumainah, Nanda Dila Zahrotul; Masamah, Ulfa (Jurnal Pendidikan Matematika Universitas Lampung, 2024)
Students with dyscalculia often face difficulties in solving mathematical problems, thus requiring an analysis of their problem-solving abilities to understand the barriers at each stage of the problem-solving process. This study aims to analyze the problem-solving abilities of students with dyscalculia in solving Islamic integration problems, based on Polya's theory, which includes four stages: understanding the problem, planning a solution, carrying out the plan, and checking the results. This study uses a case study method with a qualitative approach and was conducted at a Madrasah Tsanawiyah in Pasuruan Regency. The subjects of the study were two students with dyscalculia, NS and FA, analyzed through tests, interviews, and documentation. The results show that at the stage of understanding the problem, FA was able to identify relevant information, while NS struggled to recognize the information provided in the Islamic integration problems. Both also had difficulty in planning, identifying strategies, and proposing alternative solutions due to limited number sense. At the implementation stage, both often made calculation and procedural errors. The checking results stage was almost not performed due to difficulty in connecting the final results with the context of the problem. These findings emphasize the importance of developing more specific learning strategies for students with dyscalculia in solving Islamic integration problems, such as visual-based approaches, scaffolding, and more intensive guidance.